1993
DOI: 10.2169/internalmedicine.32.598
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Mononucleosis with Mixed Cryoglobulinemia Presenting Transient Pseudothrombocytopenia.

Abstract: A 61-year-old manwas admitted to our hospital because of fever and general malaise. We diagnosed his condition as cytomegalovirus (CMV)mononucleosis by hematological testing. His platelet count was decreased in spite of collection with several anticoagulants at room temperature (20°C) ; no decrease was observed at 37°C. Mixed cryoglobulinemia, monoclonal IgM and polyclonal IgG, which acted as anti-platelet antibodies in cold condition, were found in the patient's serum. With the resolution of CMVinfection, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 11 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…Many HIV þ and HIV ¹ haemophilia patients suffer from chronic viral infections such as hepatitis B, cytomegalovirus (CMV), Epstein-Barr virus (EBV), etc., that are able to induce anti-lymphocyte autoantibodies of the IgM type [29][30][31]. Conceivably, a decrease in IgM-coated CD4 þ lymphocytes reflects the application and efficiency of improved treatment protocols against viral infections during the past years.…”
Section: Discussionmentioning
confidence: 99%
“…Many HIV þ and HIV ¹ haemophilia patients suffer from chronic viral infections such as hepatitis B, cytomegalovirus (CMV), Epstein-Barr virus (EBV), etc., that are able to induce anti-lymphocyte autoantibodies of the IgM type [29][30][31]. Conceivably, a decrease in IgM-coated CD4 þ lymphocytes reflects the application and efficiency of improved treatment protocols against viral infections during the past years.…”
Section: Discussionmentioning
confidence: 99%
“…EDTA-PTCP occurs in both healthy subjects and patients with various diseases, with an incidence of approximately 0.1% [3,4]. In only a few cases is transient availability of EDTA-PTCP described [5,6]. In the following description of a patient after gastrectomy we observed an additional case of transiently appearing EDTA-PTCP.…”
Section: Introductionmentioning
confidence: 81%
“…Only in a few case reports regarding EDTA dependent pseudothrombocytopenia, with the underlying illness of acute hepatitis, acute myeloid leukemia, sepsis and cytomegalovirus infection, was the subsequent disappearance of EDTA-dependent platelet clumping after treatment observed [1,5,6,13,14]. Berkman et al [15] demonstrated that the appearance of pseudothrombocytopenia is related to hospitalization and the severity of illness of patients, suggesting that EDTA dependent pseudothrombocytopenia might be an acquired phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Several complications or associated manifestations have been described in immunocompetent patients with CMV infection, including severe pneumonia, granulomatous hepatitis [7], Guillain–Barré syndrome [8], meningoencephalitis [9], myocarditis [10], thrombocytopenic purpura [11], erythema nodosum [12], crioglobulinaemia [13], vasculitis [14], vascular thrombosis [15] and colitis [16]. Protracted CMV infections with malaise, fever and persistent lymphocytosis have been described in infants [17], but we are not aware of reported cases of CMV mononucleosis as a cause of protracted fever with prominent weight loss in immunocompetent adults.…”
Section: Laboratory Data On Admission For Patients In Groupmentioning
confidence: 99%